Certain Bound for q-Starlike and q-Convex Functions with respect to Symmetric Points - C. Ramachandran; D. Kavitha; T. Soupramanien (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to establish the coefficient estimates for the subclasses of q-starlike and q-convex functions with respect to symmetric points involving q-difference operator. Also certain applications based on these results for subclasses of univalent functions defined by convolution are given.